Non-surgical methods for the correction of the hump and the tip of the nose - Szpiech, Kamil; Gierszon, Patrycja; Szpiech, Andrzej; Kozioł, Maciej; Łuczyk, Robert Jan (Journal of Education, Health and Sport, 2018)
Introduction: It can be said that the nose is the most characteristic element of every face. It occupies one third of the middle part of the face. For this reason, it is very important in creating face profile. In addition, its distortions are important due to the aesthetic appearance of the face, which in turn can significantly affect the personal and professional life of a person. In aesthetic medicine, mainly non-surgical methods of correction of the hump and the tip of the nose are preferred. For this purpose, special substances called hyaluronic acid and botulinum toxin are used. Aim of the study: The aim of this study is to present non-surgical methods of correction of the hump and the tip of the nose. Materials and methods: The research method is an analysis of the literature on the subject of contemporary trends in aesthetic medicine. Conclusions: In conclusion, it should be stated that the use of hyaluronic acid or botulinum toxin allows you to quickly achieve the effect without having to undergo a complicated surgery. In addition, these are solutions with a much lower risk than in the case of surgical methods. Key words: nose, hyaluronic acid, botulinum toxin